1996
DOI: 10.1086/647338
|View full text |Cite
|
Sign up to set email alerts
|

Guideline for Prevention of Intravascular-Device–Related Infections

Abstract: The “Guideline for Prevention of Intravascular Device-Related Infections” is designed to reduce the incidence of intravascular device-related infections by providing an over view of the evidence for recommendations considered prudent by consensus of Hospital Infection Control Practices Advisor y Committee (HICPAC) members. This two-part document updates and replaces the previously published Centers for Disease Control's (CDC) Guideline for Intravascular Infections (Am J Infect Control 1983;11:183-199). Part I,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
60
1
10

Year Published

1999
1999
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(72 citation statements)
references
References 355 publications
1
60
1
10
Order By: Relevance
“…17,18,21 The aim of our study was to estimate the overall increased hospital stay and costs attributable to hospitalacquired, laboratory-confirmed BSIs. Consequently, in the results, we did not distinguish whether these were catheter related.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…17,18,21 The aim of our study was to estimate the overall increased hospital stay and costs attributable to hospitalacquired, laboratory-confirmed BSIs. Consequently, in the results, we did not distinguish whether these were catheter related.…”
Section: Discussionmentioning
confidence: 99%
“…The overall incidence and pathogen-specific rates of hospital-acquired, laboratory-confirmed BSI were similar to those observed in large teaching hospitals elsewhere. 21,[24][25][26] The method used to select patients for the study was designed not to estimate the incidence of hospital-acquired, laboratory-confirmed BSI, but rather to obtain a representative sample of adult cases of hospital-acquired, laboratory-confirmed BSI in a busy teaching hospital. It is possible that some cases were undiagnosed or were treated or died before diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 This is hazardous for patients, especially if the phlebotomist does not hand wash and scrub fingernails before gloving 2 and uses an unsterile gloved finger of the nondominant hand to guide the needle accurately into a selected vein after sterile preparation of the venipuncture site. 24 A safer way to avoid venipuncture contamination and protect phlebotomists from touching blood during IV access procedures might be outlined as follows:…”
Section: To the Editormentioning
confidence: 99%
“…They are the cause of considerable morbidity and mortality, prolonged hospital stays and an increased cost [16,17] of up to € 3,700 per episode [2].…”
mentioning
confidence: 99%